Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Pembelian di Kedai Kopi Tjan Harapan Indah Bekasi - Nikolas Isnawan; Vina Meliana (UNIVERSITAS KALBIS, 2022)
This study to determine the effect of the marketing mix purchasing decisions at Tjan Harapan Indah Coffee Shop Bekasi. The type of research used in this research is to use quantitative methods. In this research, sampling technique is purposive. The target sample in this study was 235 respondents who had come and saw the promotion of Tjan’s Coffee Shop on Instagram. The technique used in this research is purposive sampling which is part of non-probability sampling. The research data analyzed using SPSS 25 shows that the results on the marketing mix variable have a significant effect purchasing decisions.